Estimación del área foliar de la palma de pejibaye (Bactris gasipaes H.B.K.) - Clement, Charles R. (1985)
In the African oil palm, leaf area is correlated to production, and nondestructive methods of estimating area have been developed. It may be assumed that this is true for pejibaye (Bactris gasipaes). In a test of these methods and a modification of one of them for use with pejibaye, leaflet areas were regressed against leaflet length by maximum width. These coefficients were found to be constant within and between trees, and averaged 0.72. Leaflet sub-samples were found to be equal to average data. Leaf area was regressed against length by maximum width of different leaflet sub-samples times the number of leaflets. The different methods tested produce regression coefficients with little variaton between them. Use of these coefficients to estimate the area of another leaf of the same tree gave good results, as did the use of the average regression coefficient for each method. Since it is also easier to use on pejibaye, this modification is recommended for future studies. This coefficient, for use in Central American pejibaye, is 0.583.